Left ventricular aneurysm rupture as serious complication of myocardial infarction - Mak, Marek; Skiba, Jacek; Kuc, Alicja; Gemel, Marek; Król, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Left vetricle free wall rupture with aneurysm, ventricular septal defect and a huge left ventricle thrombus, a rarely diagnosed condition intra vitam. A case report concluding with a succesful cardiosurgical intervention and complete recovery.